(untitled) (World Bulletin of Management and Law, 2024)
In this article, the author covered issues such as the judges who performed judicial activities in the history of our statehood, their rights and obligations based on Fakhruddin Uzgandi’s work "Fatavoi Qazikhan". The work covers all areas of Islamic law according to its content. The article provides information about the rights and obligations of a judge, aspects that he should pay attention to when conducting his activities